SCENARIOS OF MIGRATION WITHIN THE EAEU IN CONDITIONS OF ENHANCING ECONOMIC INTEGRATION - RYAZANTSEV, Sergey; TER-AKOPOV, Alexander; PISMENNAIA, Elena; KHRAMOVA, Marina (CENTRAL ASIA AND THE CAUCASUS, 2017)
The article presents two scenarios for the development of the migration situation in the Eurasian Economic Union: extensive and intensive. In the extensive scenario of the development of the migration situation in the EAEU, the prospects for the geographical expansion of the Eurasian Economic Union are considered, and the impact of expansion on labor migration flows and socioeconomic consequences for the countries entering the Union is estimated. The prospects and effects are evaluated for the Republic of Tajikistan joining the EAEU. The authors indicate that further expansion of the Eurasian Economic Union must be based on close cooperation with other countries and integration associations. In the intensive scenario, the prospects for widening the economic integration of the participating countries are considered, as well as the prospects for creating a single labor market for highly skilled specialists in the EAEU on the basis of a unified innovation infrastructure and a single educational environment. The transition of integration projects in the post-Soviet space to its broader forms is limited by national and economic interests of the active and potential members of integration associations. Stabilization of the single labor market of the EAEU can occur, given the increasing quality, rather than quantity, of the workforce, the growth of its professional qualifications, and the increase in the transparency of migration flows. The low level of professional training not only narrows the job opportunities of labor migrants in external labor markets, but also leads to the aggravation of socioeconomic problems. It is important to create the necessary comfortable conditions for the immigration of highly qualified specialists within the framework of the EAEU. There is a need to stimulate the development of innovative infrastructure and create a single educational environment, which will result in the formation of a single labor market of highly qualified specialists. The creative economy raises the level of requirements for the qualification of workers in the labor market and, thereby, stimulates the migration of qualified employees. It is important not to allow a “brain drain” from the EAEU member states to third countries. The formation of a knowledge economy in the EAEU is able to solve a number of socioeconomic problems.